The effect of an upper body strength program on intercollegiate baseball throwing velocity - Lachowetz, T.; Evon, J.; Pastiglione, J. (The Journal of Strength and Conditioning Research, 1998)
Twenty-two college baseball players participated in a study designed to examine the effect of upper body strength training on the velocity of a thrown baseball. The treatment group received 8 weeks of strength training while the control group received no training during the fall portion of the preseason. Throwing velocity was measured for 19 players using a radar gun. Differences in mean throwing velocity were calculated for both groups.